Alprazolam induces anterograde amnesia for contextual fear memory and alters dorsoventral hippocampal neuronal ensembles in female mice - Kameron Kaplan; Lainey B. Toennies; Holly C. Hunsberger (Scientific Reports)
Abstract Benzodiazepines (BZDs) are commonly prescribed anxiolytic drugs that act on GABAa receptors, and can result in anterograde amnesia, or the inability to form new memories. While BZDs have been used for decades, the brain regions and neuronal mechanisms responsible for this detrimental side effect are largely unknown at the systems neuroscience level. To analyze the effects of BZDs on long-term memory, activity-dependent ArcCreERT2 x eYFP mice were injected with Alprazolam 30 min prior to a 3-shock contextual fear conditioning (CFC) procedure and encoding ensembles were tagged with eYFP. Mice were re-exposed to the same context 5 days later, and retrieval cell activation was analyzed using the immediate early gene (IEG), c-Fos, allowing us to determine which brain regions undergo changes after alprazolam injection. Additionally, we address the question of whether alprazolam induces state-dependent memory by altering the timelines of injection. We found that 1) alprazolam treated male and female mice exhibit a decrease in memory retention after conventional CFC and, 2) alprazolam treated female and male mice show a decrease in memory retention in a state dependent CFC timeline with a saline injection prior to re-exposure, 3) alprazolam treated female mice exhibit increased EYFP + (encoding) activation in the dCA1 and enhanced engram activation in the dCA3, and 4) alprazolam treated females showed less c-Fos + activation in the vCA1. These results suggest that alprazolam induces sex-specific ensemble activation throughout the hippocampus and will help us understand the long-term memory deficits associated with BZD use.